A sparse stacked denoising autoencoder with optimized transfer learning applied to the fault diagnosis of rolling bearings. (November 2019) - Sun, Meidi; Wang, Hui; Liu, Ping; Huang, Shoudao; Fan, Peng
Highlights: Fault diagnosis by stacked autoencoder requires less professional knowledge. Domain adaptation by optimized transfer learning reduces the algorithm's complexity. Stronger feature extraction ability improves the accuracy of diagnosis. Combined algorithm can be better applied to the target domain in fault diagnosis. Abstract: Fault diagnosis is an important technology in the development of modern industrial safety. Vibration information is commonly used to determine the state of bearings. Driven by big data, deep learning brings new opportunities to fault diagnosis. As an unsupervised deep learning algorithm, a stacked autoencoder (SAE) can relieve the pressure of labelling data. Due to the diversity and variability of the actual fault diagnosis distribution, an optimized transfer learning (TL) algorithm is proposed to solve the domain adaptation. By directly inheriting features obtained from the pre-training process in the source domain and changing only the fine-tuning process, the complexity of the algorithm is reduced. Considering the data reconstruction ability and robustness, a sparse stacked denoising autoencoder (SSDAE) is proposed for feature extraction, which can indirectly improve the diagnostic accuracy in the target domain. The results for data from the Case Western Reserve University Bearing Data Center show that the proposed SSDAE-TL algorithm is feasible and easy to implement for the fault diagnosis of bearings.